2017
DOI: 10.1146/annurev-cellbio-100616-060531
|View full text |Cite
|
Sign up to set email alerts
|

The Three-Dimensional Organization of Mammalian Genomes

Abstract: Animal development depends on not only the linear genome sequence that embeds millions of cis-regulatory elements, but also the three-dimensional (3D) chromatin architecture that orchestrates the interplay between cis-regulatory elements and their target genes. Compared to our knowledge of the cis-regulatory sequences, the understanding of the 3D genome organization in human and other eukaryotes is still limited. Recent advances in technologies to map the 3D genome architecture have greatly accelerated the pac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
284
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 332 publications
(294 citation statements)
references
References 138 publications
6
284
0
Order By: Relevance
“…There is evidence that TAD boundaries act as genetic insulators, ensuring appropriate enhancerpromoter interactions (Dixon et al 2012;Krivega & Dean 2017). Disruption of TAD boundaries can lead to increased interactions between TADs, resulting in an altered phenotype (Yu & Ren 2017;Furlong & Levine 2018).…”
Section: Candidate Genesmentioning
confidence: 99%
“…There is evidence that TAD boundaries act as genetic insulators, ensuring appropriate enhancerpromoter interactions (Dixon et al 2012;Krivega & Dean 2017). Disruption of TAD boundaries can lead to increased interactions between TADs, resulting in an altered phenotype (Yu & Ren 2017;Furlong & Levine 2018).…”
Section: Candidate Genesmentioning
confidence: 99%
“…The 3D spatial organization of the chromosomes in the nucleus of eukaryotic cells appears to be cell type specific [1][2][3][4][5][6][7]. What determines this cell type specific organization and how that organization relates to patterns of gene expression remain crucial questions in structural genomics.…”
Section: Introductionmentioning
confidence: 99%
“…The relationship between transcription and the 3D chromatin structures is one of the most fundamental questions in the post-genomic era [1][2][3][4]. Mounting evidence has shown that transcription activities correlate with more DNA interactions in development and diseases [5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%